Selfmoordneigings en selfdestruktiewe gedrag tydens adolessensie: 'n gestaltterapeutiese riglyn - Swanepoel, G; Joubert, JMC (Social Work/Maatskaplike Werk, 2001)
This research study is concerned with exploring suicide orientated behaviour that manifest during adolescence. The goal of this study was to determine the impact of a gestalt therapeutic guideline by using projective techniques, in order to create alternative behaviour for the self-destructive ways in which these suicide orientated adolescents are trying to communicate their messages and express themselves emotionally. In order to achieve this goal, projective techniques within the gestalt approach such as drawings, clay, music, role-play and the diary were used to help these adolescents communicate their feelings in a more constructive way, get control of their lives and achieve gestalt homeostasis. Applied research was used, in order to make the research results applicable on the practice problem namely suicide orientated behaviour during adolescence, and to provide solutions and alternatives for this behaviour. Two respondents were selected with a goal directed sample, with which six individual gestalt therapeutic sessions each was held. A research hypothesis was made namely that, if a gestalt therapeutic guideline can be done with the potential adolescent who will commit suicide where he can be empowered to be self supportive, express self-destructive feelings and identify alternative behaviour for it, then he will be able to feel less hopeless, helpless and depressed and would be less inclined to end his life. A pre and post test was done with the aid of the ISO-30 measurement scale, in order to determine the impact and success of the guideline, with reference to the suicide orientated adolescent's behaviour and thoughts. The research results from the therapeutic intervention as well as the ISO-30 scale, confirmed the hypothesis as true. The adole·scents were very suicide orientated and blocked in regard to alternatives for their self-destructive behaviour, with the start of the sessions. After the gestalt guideline was done, a fundamental decrease in feelings of helplessness and suicide orientation was observed. The cardinal influence and value of a preventional gestalt guideline is evident, in terms of addressing suicidal behaviour during adolescence.